Pharmacological modulation of histone demethylase activity by a small molecule isolated from subcritical water extracts of Sasa senanensis leaves prolongs the lifespan of Drosophila melanogaster - Nakagawa-Yagi Yuzo; Sato Yukiko; Matsumoto Emi; Nakatsuka Shin-ichi; Sakaki Tsuyoshi; Muramatsu Yukiko; Hara Takaaki; Aigaki Toshiro (BMC, 2012)
Abstract Background Extracts of Sasa senanensis Rehder are used in traditional Japanese medicine; however, little is known about the underlying mechanisms of their potential health benefits. Methods S. senanensis leaves were extracted with subcritical water. An active small-molecule was isolated using reversed-phase high-performance liquid chromatography (HPLC), and identified as 3,4-dihydroxybenzaldehyde (protocatechuic aldehyde or PA). The effects of PA on the activity of histone demethylase, the Drosophila melanogaster lifespan and gene expression in Drosophila S2 cells were investigated. Results PA inhibited the activity of Jumonji domain-containing protein 2A (JMJD2A) histone demethylase in a dose-dependent manner with a half-maximal inhibitory concentration (IC50) of 11.6 μM. However, there was no effect on lysine-specific demethylase 1 (LSD1), histone deacetylase 1 (HDAC1) or HDAC8. PA significantly extended the lifespan of female, but not male, Drosophila. In Drosophila S2 cells, the eukaryotic translation initiation factor 4E binding protein (4E-BP) was up-regulated by PA exposure. Conclusions Our findings provide insight into the possible relationship between the pharmacological modulation of histone demethylation and lifespan extension by PA; they might also be important in the development of alternative therapies for age-related disorders.